The Development of Public Finance Curriculum at Institute of Home Affairs Goverance (IPDN) in the Ministry of Home Affairs: A Scoping Literature Review - Sinurat, Marja (Journal of Ecohumanism, 2024)
The absence of a complete platform related to the development of the public finance curriculum in government institutions, the impact of the absence of a "blueprint" of the emergence of unclear resources that have not been competent both in knowledge, relatedness and autonomy. The purpose of the need for a curriculum development framework from the results of a philosophical, ontological and methodological literature review. A systematic search was conducted on electronic databases, namely Science Direct, PubMed, and Taylor and Francis. Data analysis was conducted using PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Study results were mapped based on the following criteria: 1) conceptual analysis; 2) predictor factors; and 3) Examination in varios fileds and the global development of curriculum public finance Research. A total of 48 articles met the inclusion and eligibility criteria for further review in this scoping literature review. The philosophical framework as a platform includes the theoretical framework, public finance curriculum model, delivery strategy, management strategy, and public finance curriculum framework. guide to the preparation of the official higher education curriculum in the industrial era 4.0. The public finance integrated curriculum is a combination of the official curriculum and the Ministry of Education and Culture Curriculum. The Public Finance Curriculum implemented by Institute of Governance of Home Affairs (IPDN) focuses on regional finance with attitude development, both social attitudes and spiritual attitudes. The coverage of the public finance curriculum litelature has implications for providing a comprehensive analysis of the impact of the integrated curriculum through education, training and nurturing philosophically, ontologically and methodologically, besides that the framework of the research results can be used by policy makers related to curriculum stakeholders, resources and regulations as a basis for implementing platforms built on the basis of theoretical data analysis to support strategies, implementation in the civil service education environment.